Role of Female in Agriculture Related to Work Performance and Decision Making in Madi, Chitwan, Nepal - Dhakal, Roshan; Jha, Ritesh Kumar; khadka, Rita; Koirala, Roshan; Neupane, Rojina (International Journal of Applied Sciences and Biotechnology, 2018)
This research is a study to examine whether a “feminization of agriculture” has occurred in the study area through the household survey of the local farming system and the gendered division of agricultural labour and managerial responsibilities at Madi, Chitwan in 2018. According to the household survey (n=60), a strong gendered division of agricultural works exist in this area, thus men and women have clear responsibilities and restrictions. In activities like ploughing, irrigating, threshing and applying chemical fertilizer, men are mostly participated whereas in the most of the other activities like weeding, sowing, collecting firewood, collecting fodder, hoeing, manuring, milking, female are mostly involved. Average of about 208 rupees is paid higher to men than female in some agriculture works. Through the use of various fieldwork methods, it was observed that that women in some cases have to take on tasks that are generally considered “men’s work”. Although women are in charge of various managerial decisions related to the agricultural production, any major decisions are still controlled by men. The real influence of women as decision makers can therefore be questioned. The effects of different factors like caste, education and training has been analyzed which showed that with the increase of education and training, feminization in decision making role is increased. But if women get more work and just involved in the feminization of labour and no influence in decision-making processes the “feminization of agriculture” will be just a female exploitation not a feminization. Int. J. Appl. Sci. Biotechnol. Vol 6(3): 207-214